Iddah Bagi Suami Karena Cerai Mati dalam Kajian Filsafat Hukum Islam - Muhammad Nur Kholis Al Amin (Kopertais Wilayah III Yogyakarta, 2016)
Islamic law provides thorough coverage of rules applicable in the various fields of the Muslim community, is no exception in the case of marriage that included also the process of pre-wedding until the end of a marriage which is called talak or divorce. As for the divorce can be caused due to rupture of the sacred or be caused due to a death of one ot them, namely “cerai mati”. This has an impact with their concept of the iddah for a woman who explicitly described in the Qur’an, while the iddah for husband absolutely nothing in the theachings of Islam explicitly, whereas some people view that there are “moral ethical” if the iddah imposed for a husband because “cerai mati”. Therefore, through the Philosophical approach of Islamic Law—which contains three main values, namely: certainty, fairness, usefulness/ benefit—this article will try to find answer to the concept of iddah imposed for husband.